The A98V single nucleotide polymorphism (SNP) in hepatic nuclear factor 1 alpha (HNF-1alpha) is associated with insulin sensitivity and beta-cell function - Bergmann, A; Li, J; Selisko, T; Reimann, M; Fischer, S; Grässler, J; Schulze, J; Bornstein, S R; Schwarz, P E H (Experimental and clinical endocrinology & diabetes, 2008)
Mutations in the hepatic nuclear factor-1-alpha ( HNF-1alpha) gene is considered as a candidate for the aetiology of type 2 diabetes. The aims of the study was to determine whether two single nucleotide polymorphisms (SNPs) ile27-to-leu and ala98-to-val in the HNF-1alpha gene associate with diabetes, insulin sensitivity as well as beta-cell function. 1 479 subjects of a volunteer sample with increased risk of type 2 diabetes were investigated. They underwent a 75 g oral glucose tolerance test (OGTT) with measurements of plasma glucose, insulin and C-peptide at fasting and at 30, 60, 90 and 120 minutes after the glucose challenge. The HNF-1alpha SNPs, I27L and A98V were genotyped. Patients harbouring the V98 allele exhibited higher serum insulin and C-peptide levels. The heterozygote variant was also associated with decrease in beta-cell function but better insulin sensitivity. No significant differences of any clinical parameters were found for I27L gene variants. Significant associations between the heterozygote A98V genotype and clinical parameters of insulin metabolism were reported but no relationship with type 2 diabetes was obtained. This may be explained by a balancing negative effect on insulin secretion and concomitant positive effect on insulin resistance in Val allele carriers.